2020
DOI: 10.3390/su12051840
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prioritized Natural Landscape Conservation Areas for National Park Planning in China

Abstract: Protecting representative natural ecosystems, rich biodiversity, and unique natural landscapes are the main considerations in China's national park planning. Here, we mapped the distribution of China's natural landscapes and evaluated their protection values for national park planning and construction. Grading evaluation methods combining standard comparison, inventory method, and expert consultation were used, and four levels of natural landscapes were identified. Furthermore, priority areas for national park… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…With regard to the hierarchical framework for landscape conservation, Francesca Nocca et al directly established frameworks based in the literature where the former took cities as the research scope, trying to find out the relationship between landscape variation and wellbeing variation, and the latter took natural landscape conservation areas countrywide as the research scope, evaluating the status of natural landscapes in China based on the criteria of typicality, aesthetics, authenticity, integrity, and historical and cultural values [10,61]. Vassiliki Vlami et al established frameworks based on a combination of literature review and extensive field trials, taking an island as the research scope to diagnose a holistic landscape for the purpose of conservation instead of evaluating from the perspective of traditional visual aesthetics [62].…”
Section: Hierarchical Framework Of Historic Districts Tourism Attractiveness and Landscape Conservationmentioning
confidence: 99%
“…With regard to the hierarchical framework for landscape conservation, Francesca Nocca et al directly established frameworks based in the literature where the former took cities as the research scope, trying to find out the relationship between landscape variation and wellbeing variation, and the latter took natural landscape conservation areas countrywide as the research scope, evaluating the status of natural landscapes in China based on the criteria of typicality, aesthetics, authenticity, integrity, and historical and cultural values [10,61]. Vassiliki Vlami et al established frameworks based on a combination of literature review and extensive field trials, taking an island as the research scope to diagnose a holistic landscape for the purpose of conservation instead of evaluating from the perspective of traditional visual aesthetics [62].…”
Section: Hierarchical Framework Of Historic Districts Tourism Attractiveness and Landscape Conservationmentioning
confidence: 99%
“…Experts recommend identifying priority areas for PNP inclusion through careful evaluation of science-based criteria and indicators. One study has already evaluated protection values of China's natural landscapes and identified over 8% of the country's landmass as priority areas for park planning [81], and another noted a 19% spatial mismatch of priority areas with current nature reserve locations [82]. It has been emphasized that prospective national parks should establish scientific research bases for further environmental or ecological studies that contribute to their sustainability [72].…”
Section: Key Guiding Principles and Reform Mechanismsmentioning
confidence: 99%
“…However, the introduction of the PNP initiative has been criticized for not explicitly addressing reforms to the CPA system and for an apparent lack of centralized leadership [93]. The following issues have been identified by professionals (e.g., [19,79,81]) as key considerations to future national park management:…”
Section: Future Considerations In China's Pilot National Parksmentioning
confidence: 99%
“…National parks are established to play a vital role in the national nature reserve system. The healthy ecosystem of national parks is conducive to protecting biodiversity and promoting human development [ 10 ]. A comprehensive assessment of national park ecosystem health is needed for the construction of high-quality national parks [ 11 ].…”
Section: Introductionmentioning
confidence: 99%